PWE-329 A potential role of braf mutation immunohistochemistry in the investigation and treatment of anal melanoma. (22nd June 2015) - Jones, HG; Egan, R; Davies, M; Harris, D; Khot, U; Chandrasekaran, T; Hatcher, O; Gwynne, S; Maw, K; Williams, N; Evans, M; Beynon, J
Abstract : Introduction: Malignant melanoma of the anal mucosa is a rare and aggressive cancer. There is very little evidence about the optimal investigation and treatment of this condition. The aims of this study were to investigate the prevalence of BRAF mutation in anal melanoma (AM), compared to that of the cutaneous form of the disease (BRAF mutation present in around 60% of cases). Secondary objectives were to assess overall survival and recurrence rates after abdomino-peroneal excision (APE) versus wide local excision (WLE). Method: An observational study with retrospective data collection was conducted on all patients coded with AM on the local pathology system. Data were collected on patient demographics, radiological investigations, local and systemic therapies, pathological reports and mortality and morbidity. BRAF mutation was assessed through a newly validated immunohistochemistry (IHC) assay. Results: Nine patients were diagnosed with AM over the study period, 7 had tissue available for BRAF IHC. There were five men, and two women, with a median age of 66 years (range 48–74). The mortality rate was 71.4% (5 of 7 patients), with a one and two-year survival of 57% and 29% respectively. Of the seven patients tested for a BRAF mutation, one (14%) tested positive for a mutation in the BRAF gene on IHC. Conclusion: AM is an extremely aggressive cancer with very poor prognosis. This study demonstrated a low incidence of BRAF mutation in AM, which suggests that kinase inhibitors such as Vemurafenib will have little impact on the treatment and prognosis of this condition. Disclosure of interest: None Declared.